Pemeriksaan Telur Cacing Trichuris Trichiura Pada Spesimen Feses Siswa TK Mutiara Di Waiheru Kota Ambon - Damayanti Sima Sima Sohilauw; M Fadly Kaliky (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Trichuris trichiura egg infection or commonly called whipworm in children is a mild and severe helminthiasis infection. Mild infection does not give obvious clinical symptoms so fecal examination must be done. Therefore, it is important to perform diagnostic techniques which is one of the important aspects to determine the presence of helminth infection, which can be established by identifying and recognizing the stage of the parasite found. The purpose of this study was to determine the results of Trichuris trichiura eggs examination in feces specimens of Mutiara Kindergarten students in Waiheru, Ambon City. The method used in the descriptive research design where the analysis technique uses laboratory tests, with a total sample of 35 Mutiara Kindergarten Students in Waiheru Ambon City, using Consecutive sampling technique. The results showed that out of 35 samples of Mutiara kindergarten children, there was 1 person who had Trichura trichiura worms. The conclusion is that the research conducted on the examination of worm eggs using the Kato katz method in the feces of Mutiara Kindergarten Students in Waiheru Ambon City resulted in 1 positive student with Trichuris trichiura worms.